Literasi Media Sosial bagi Millenials dalam Mempromosikan Pariwisata Lombok Pasca Gempa Agustus 2018 - Siti Chotijah (Universitas Mathla'ul Anwar Banten, 2020)
SOCIAL MEDIA LITERACY FOR MILLENNIALS IN PROMOTING TOURISM IN POST-EARTHQUAKE LOMBOK IN AUGUST 2018. After the earthquake in Lombok in August 2018 there was a significant decline in the number of tourists. The decline in the number of visits has an impact on the potential of NTB Province's original income as well as the growth of the economic sector which is supported by tourism activities. This is caused by the amount of hoax information that appears in various media, especially social media. Various information on this hoax makes tourists fail to come to Lombok because they feel worried, anxious and afraid if aftershocks occur. The fact is that there was a small earthquake several times after August but it was not significant and did not cause damage like last August 2018. Lombok is currently declared safe, but various news related to Lombok are not completely clear of the theme of disaster. The behavior of netizens, especially millennials, is not yet fully conditioned and supports the promotion of Lombok tourism, especially in the promotion of post-earthquake events. Many do things they shouldn't do and lead to negative content. For this reason, social media literacy is needed, especially for millennials in promoting Lombok tourism after the 2018 earthquake in August, considering millennials are the most active and responsive in social media.